BIOLOGICAL WASTEWATER TREATMENT USING HIGHER AQUATIC PLANTS (Scientific journal of the Fergana State University, 2024)
This article presents the results of research on the biological treatment of various industrial and domestic wastewater using higher aquatic plants. The experiments examined the possibility of biological treatment of mining wastewater on a semi-industrial scale using Eichhornia crassipes Solms, Pistia stratiotes L. Azolla caroliniana and Lemna minor and their features in biological treatment are identified. Eichhornia and pistia plants are important because they show high efficiency in wastewater treatment due to their high adsorption properties, with frequent renewal of biomass in ponds, the phytoremediation capacity of higher aquatic plants is 51% per day due to the adsorption properties of plants, based on calculations, it is possible to propose cleaning pools with a volume of 1000 cubic meters of water for 5 days, through the renewal of plant culture every 1-3 days.